ANALISIS LOYALITAS PELANGGAN HOTEL SYARIAH DI DAERAH ISTIMEWA YOGYAKARTA - Kristianto, Dwi Agus; Kiswantoro, Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
In the past the function of the hotel was only as a place to stay for consumers who travel on business or tourism and do not have a relationship or family at their destination. Sharia concept hotels continue to grow along with the needs of Muslim consumers around the world. The concept of sharia hotels also continues to grow in Indonesia, especially in the Yogyakarta region as one of the tourist destinations in Indonesia. This study aims to determine the effect of price, service quality and brand image on customer loyalty of sharia hotels in Yogyakarta Special Region both partially and simultaneously.This type of research is causally comparative. The variables in this study are price, service quality, brand image and customer loyalty. The population in this study are customers who have visited sharia hotels in Yogyakarta. Sampling was done by nonrandom sampling, specifically using purposive sampling where the sample was taken from the population, with the following criteria: 1) Customers who had stayed in sharia hotels in Yogyakarta more than twice, and 2) Respondents aged 18 years. The sample in this study was taken as many as 100 respondents. Data collection techniques using questionnaires. Data analysis used is multiple linear regression analysis.Based on the results of the study, the following conclusions are obtained: (1) Prices have a positive and significant effect on customer loyalty; (2) Service quality has a positive and significant effect on customer loyalty; (3) Brand image has a positive and significant effect on customer loyalty; and (4) Price, service quality, and brand image have a positive and significant effect on customer loyalty. Keywords: hotel, sharia, price, service quality, brand image, customer loyalty.